The Influence of Service Quality on Loyalty of Class 3 Inpatient Patients at Muhammadiyah Hospital Bandung - Supriyati Supriyati; Fransiska Agustina (Sean Institute, 2024)
This study aims to examine the influence of service quality on the loyalty of class 3 inpatients at Muhammadiyah Hospital in Bandung. To test this hypothesis, this research uses a survey method using a questionnaire involving 73 respondents and statistical analysis. The research results show that the variables responsiveness and assurance have a significant influence on patient loyalty. Patients who feel cared for and have confidence in the quality of services provided tend to feel more loyal to Muhammadiyah Hospital Bandung. This shows the importance of service quality in increasing patient loyalty, which in turn can increase patient satisfaction and hospital operational efficiency.